FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO AUDIT DAN KECURANGAN LAPORAN KEUANGAN: PENGENDALIAN INTERNAL, AUDIT OPERASIONAL DAN KOMITMEN MANAJEMEN - Ivan El Adam; Cris Kuntadi (Bajang Institute, 2026)
Research on audit risk and financial statement fraud continues to evolve in line with increasing business complexity and organizational demands for transparency. This article is a literature review study aimed at identifying and analyzing the factors that influence audit risk and financial statement fraud, focusing on three main variables: internal control, operational audit, and management commitment. The literature review was conducted by examining relevant previous studies, particularly from national journals indexed in SINTA, ensuring that the findings are grounded in strong academic foundations and aligned with the standards of scientific publication in Indonesia. The results indicate that effective internal control can minimize the likelihood of fraud, operational audits play a role in improving efficiency and detecting system weaknesses, while management commitment is a key factor in maintaining the integrity and accountability of financial statements. This article concludes that these three variables have a significant influence on audit risk and financial statement fraud, and provides a basis for the development of hypotheses for future research. Furthermore, this study emphasizes the need to explore other variables that may affect audit risk, so that subsequent research can offer a more comprehensive perspective